Through Feminist Eyes: Essays on Canadian Women's History - Joan Sangster (Athabasca University Press, 2011)
Through Feminist Eyes gathers in one volume the most incisive and insightful essays written to date by the distinguished Canadian historian Joan Sangster. To the original essays, Sangster has added reflective introductory discussions that situate her earlier work in the context of developing theory and debate. Sangster has also supplied an introduction to the collection in which she reflects on the themes and theoretical orientations that have shaped the writing of women's history over the past thirty years. Approaching her subject matter from an array of interpretive frameworks that engage questions of gender, class, colonialism, politics, and labour, Sangster explores the lived experience of women in a variety of specific historical settings. In so doing, she sheds new light on issues that have sparked much debate among feminist historians and offers a thoughtful overview of the evolution of women's history in Canada.